84.7k views
3 votes
Simplify the expression (picture provided)

Simplify the expression (picture provided)-example-1
User Necole
by
4.9k points

1 Answer

7 votes

Answer:

The answer is (a) ⇒
a^{(3)/(2)}bc^(2)

Explanation:

* Lets revise the rational exponent

-
\sqrt[n]{x^(m)}=x^{(m)/(n)}

* So we can change any radical to a rational exponent

* Lets solve our problem


\sqrt[4]{a^(6)b^(4)c^(8)}

* Lets simplify each one

- The first is root 4 of a to the power of 6, we will change the root

and the power to rational exponent 6/4


\sqrt[4]{a^(6)}=a^{(6)/(4)} ⇒ simplify the fraction


\sqrt[4]{a^(6)}=a^{(3)/(2)}

- The second is root 4 of b to the power of 4, we will change

the root and the power to rational exponent 4/4 = 1


\sqrt[4]{b^(4)}=b^{(4)/(4)}=b^(1)=b

- The third is root 4 of c to the power of 8, we will change

the root and the power to rational exponent 8/4 = 2


\sqrt[4]{c^(8)}=c^{(8)/(4)}=c^(2)

* The simplest form of
\sqrt[4]{a^(6)b^(4)c^(8)}=a^{(3)/(2)}bc^(2)

User Gladhus
by
4.5k points